História da educação musical e a experiência do canto orfeônico no Brasil - Wilson Lemos Júnior (EccoS – Revista Científica)
The teaching of music was always present during the periods of the history of the Brazilian education, but during the first half of the twentieth century, had a boom especially after the defense of the movement of educators of the new school, as the teachers Fernando de Azevedo and Anísio Teixeira and as the musician and conductor Heitor Villa-Lobos. In this article are discussed the process of recovery and the deployment of teaching music and chorus singing in the Brazilian schools. It tries to analyze the discourse of these characters, their ideas concerning music education, as well as their purposes, their advantages and their relations with the modern school.